Variation of Static Parameters of Cooperation in Axisymmetric Connection. (2016) - Dudziak, Marian; Domek, Grzegorz; Kołodziej, Andrzej
Abstract: During designing the profiles of construction elements are defined as a perfect shape of line, circle or cylinder etc. Due to the production process the elements macrogeometry can be distorted in many ways. The direct measure of deviation of the real shape of a part from its nominal shape (the designed one) is a form deviation. If any additional restrictions concerning form deviations are not given in a production drawing, then the influence of these form deviations should be taken into account in allowable area of dimensions variation which is defined with tolerance zone. High values of rectilinearity deviations of a generating line, roundness deviations and cylindricity deviations can be a reason of changes of the assumed functional requirements. On the basis of saddleback shafts with oval cross-sections manufactured in three accuracy classes, i.e. IT4, IT6 and IT9, the authors have presented the variation of static parameters of cooperation. The shafts were coupled with sleeves (with a nominal circular cross-section) on experimental test stand. The obtained values of friction forces and moments of friction which are necessary to disassemble the connection were compared with the results of FEM numerical analyses. The applied method also allowed to determine the values of contact pressures in a connection.